Digital constitutionalism as an online speech governance framework: A critical approach - Clara Iglesias Keller; Jane Reis G. Pereira (Digital Constitutionalism, 2025)
This chapter advances a critical approach to the theories of “digital constitutionalism”, in particular as a theoretical framework for recent initiatives targeting online speech governance. We build on previous work where we demonstrated overarching risks of borrowing from the symbolic load of the constitutionalist tradition to name and explain transnational normative phenomena that take place in private digitalised environments. We apply these critiques to the case of online speech governance by looking at two policy initiatives: the Meta Oversight Board, a private sector self-regulatory initiative implemented by the company Meta; and the European Digital Services Act. Our goal is to shed light on contradictions and misperceptions embedded in labelling online speech governance mechanisms as manifestations of digital constitutionalism.
Keywords: 300